Influence of the hydrogen saturation temperature on the structure of melt-spun Ti₃₀Zr₄₅Ni₂₅ alloy - Dmytrenko, O.Ye.; Kolodiy, I.V. (Вопросы атомной науки и техники, 2018)
The influence of hydrogen saturation temperature on the structure and phase composition of the melt-spun Ti₃₀Zr₄₅Ni₂₅ alloys, heat-treated in hydrogen atmosphere at different temperatures (400, 450, 500 °C) for 4 hours, was studied. Using X-ray diffraction analysis it was found that hydrides, formed during the hydrogenation process, were based on the Laves phase L-TiZrNi and (Ti, Zr)₂Ni, α-(Ti, Zr) phases. Structural models of these phases were constructed and a model for filling these phases with hydrogen was presented. Electron microscopic study showed that the surface of the samples had no significant changes during the hydrogenation process. Also, it was established the influence of the hydrogenation temperature on the concentration of oxygen and nitrogen gas impurities in the samples.